Fundamentals of light sources and lasers - Csele, Mark (John Wiley, 2014)
This field of photonics is finding increasing applications across a broad range of industries. While many other books provide an overview of the subject, Fundamentals of Light Sources and Lasers closes a clear gap in the current literature by concentrating on the principles of laser operation as well as providing coverage of important concepts necessary to fully understand the principles involved. The scope of the book includes everything a professional needs to get up to speed in the field, as well as all the material necessary to serve as an excellent introductory laser course for students.